Cellpackexplorer: Interactive model building for volumetric data of complex cells. Issue 2 (December 2019) - Schwarzl, Magdalena; Autin, Ludovic; Johnson, Graham; Torsney-Weir, Thomas; Möller, Torsten
Abstract: In this paper, we describe cellPACKexplorer, a system designed to help developers of cellPACK find errors in and improve their algorithm. cellPACKexplorer focuses on visualizing the effects of cellPACK recipe parameters on the final packing output. We found that the developers have two different methods for understanding the output, numerical and visual, depending on their background. We designed cellPACKexplorer with a flexible interface to support both types of users. We evaluated our tool through case studies and questionnaires. Novice users were able to create cell models with cellPACK and explore the behavior of different parameters. Further, expert users discovered an error in the code and were able to locate the problem quickly with our new analysis tool. We conclude with a discussion of the implications of our findings in the wider visualization community.